2019
DOI: 10.1186/s12879-019-3743-7
|View full text |Cite
|
Sign up to set email alerts
|

Immune signatures for HIV-1 and HIV-2 induced CD4+T cell dysregulation in an Indian cohort

Abstract: BackgroundHIV-2 infection is characterised by a longer asymptomatic phase and slower AIDS progression than HIV-1 infection. Identifying unique immune signatures associated with HIV-2 pathogenesis may thus provide therapeutically useful insight into the management of HIV infection. This study examined the dynamics of the CD4+T cell compartment, critical in disease progression, focussing on chronic HIV-2 and HIV-1 infected individuals at various stages of disease progression.MethodsA total of 111 participants in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…We observed anapparent increase in the frequency of Tregs (CD4+ CD25 high CD127 low ) in both PA and LTNP groups compared to SN controls (Figure 8A). This is in concurrence with our earlier reported data for both HIV-1 and HIV-2 infected individuals (16, 26). Expansion of Tregs exhibited a highly significant association with decline in the frequency of classical monocytes ( r = −0.7727, P < 0.01) and corresponding rise in the frequency of intermediate monocytes ( r = 0.8, P < 0.01) in PAs (Figure 8B).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…We observed anapparent increase in the frequency of Tregs (CD4+ CD25 high CD127 low ) in both PA and LTNP groups compared to SN controls (Figure 8A). This is in concurrence with our earlier reported data for both HIV-1 and HIV-2 infected individuals (16, 26). Expansion of Tregs exhibited a highly significant association with decline in the frequency of classical monocytes ( r = −0.7727, P < 0.01) and corresponding rise in the frequency of intermediate monocytes ( r = 0.8, P < 0.01) in PAs (Figure 8B).…”
Section: Resultssupporting
confidence: 94%
“…Chronic activation of the immune system is a hallmark of progressive HIV infection and frequency of activated T lymphocytes better predicts disease outcome than plasma viral load and CD4 counts alone (20, 26, 36). In our study, viral load showed a more significant association with frequency of activated CD8+ T lymphocytes (HLA-DR+CD38+) ( r = 0.6909, P < 0.05) in the PA group (Figure 7B) and frequency of activated CD4+ T lymphocytes (HLA-DR+CD38+) ( r = 0.7119, P < 0.001) in the LTNP group (Figure 7B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the frequency of these CD4 + T cell subsets was found to be similar in ART-naive and -receiving groups. These data confirm our previous findings, and extend these to the HIV-D group [37]. Also, T reg (CD25 high CD127 low ) frequency was lower, although not significantly (P = 0·0599), in ART-receiving, compared to ART-naive, HIV-1-infected individuals (Fig.…”
Section: Dysregulation In the Frequencies Of Homeostatically Significsupporting
confidence: 91%
“…For phenotypic characterization, immunostaining of 200 µl of fresh peripheral whole blood with four-color combinations of the following fluorescently labeled monoclonal antibodies, anti-CD3 (Clone:SK7), anti-CD4 (Clone: RPA-T4), anti-CD8 (Clone: SK1), anti-CD25 (Clone: M-A251), anti-CD127 (Clone: HIL-7R-M21), anti-CCR7 (Clone: 150503), anti-CD45RA (Clone: HI100), anti-HLA-DR (Clone: L243), anti-CD38-PECY5 (Clone: HIT2), anti-PD-1 (Clone: EH12.1), anti-CD28 (Clone: 28.2), and anti-CD31 (Clone: WM59), was performed as reported previously (21). Briefly, 200 µl of fresh EDTA blood was incubated with fluorescently labeled monoclonal antibodies for 20 min at room temperature.…”
Section: Immunophenotypingmentioning
confidence: 99%